The need to be unique and the innovative behavior: The moderating role of supervisor support - Bekmezci, Mustafa; Rehman, Wasim Ul; Khurshid, Muzammil; Eroğluer, Kemal; Trout, Inci Yilmazli (Frontiers in Psychology, 2022)
The purpose of this study is to examine the moderating effect of supervisor support on the relationship between the need to be unique and the innovative behavior. People not only strive to belong to a group but also want to be unique from others and feel exceptional. Individuals' innovative behavior is one of the things that makes them feel different from other people. Because developing a new idea, supporting this idea, putting this idea into practice, and the positive achievements of this idea distinguish people who exhibit innovative behavior from others. It depends on the behavior of supervisors whether people who break away from typical practices and procedures to feel unique and special continue to act in innovative ways. In this context, it is vitally essential for supervisors to support people who display innovative behavior. The research was conducted on people working in the education sector in Mersin. The Self-Attributed Need for Uniqueness Scale developed by Lynn and Harris (1997), the Innovative Behavior Scale, developed by Scott and Bruce (1994) and The Supervisor Support Scale developed by Giray and Şahin (2012) was used in this research. In this research, confirmatory factor analysis of each variable was performed, the correlation between the variables was examined, and the moderator effect was tested. As hypothesized the need to be unique had a significant and positive effect on innovative behavior. This finding is relevant to advancing previous studies on need to be unique and innovative behavior. However, it has been determined that supervisor support doesn’t have a moderator role on the relationship between the need to be unique and innovative behavior. Although there are some researches in the literature on consumer experiences about the need to be unique and innovative behavior, it has been evaluated that there is not enough research on its reflections on the workplace. This study was conducted in the education sector employees. Because we could not find any research on this subject in the education sector.